Chemotherapeutic efficacy of praziquantel and closantel in experimental porcine schistosomiasis - SHAMES, N; AGRAWAL, M C; RAO, K N (The Indian Journal of Animal Sciences, 2014)
Young piglets of local breed, weighing 2-3kg were infected by "polythene tail method" each with 1500 cercariae of Schistosoma incognitum, procured from laboratory infected snails and were divided into 4 groups. On 21 day post infection, the first group (A) was treated with praziquantel (50mg /piglet) and second; with closantel (75 mg/piglet) as a single dose therapy while third group (C) was kept as infected untreated control. Additionally fourth group CD) was kept as uninfected control. These infected piglets were sacrificed on 26 to 31 day post-treatment; perfusion technique with microscopic examination of all the tissues for blood fluke recovery and egg load was followed in all the animals. The average fluke recovery was 62.6 flukes/ animal in untreated control with 25.0 and 40.8 flukes/ animal in praziquantel and closantel treated groups resulting in 60.06 and 34.82% fluke reduction respectively. The egg load reduction in lungs, liver and intestine was also between 38 and 80% in the treated groups. Statistically these reductions were insignificant.